Pengetahuan Masyarakat Tentang Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan di Kelurahan Sananwetan - Sunarti Sunarti; Anita Putri Agustina (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
Social Security Administering Agency (BPJS) of health is legal entitythat are created to hold the health insurance. The participants of health insurance usually do not care about their health because they do not understand about the BPJS management. In consequence, it created problem and complain and insatisfaction. The purpose of the research was to know the knowledge of people about Social Security Administering Agency (BPJS) of health in Blitarcity. The design was descriptive. the sample was 100 head of the families using quota sampling technique. Data collection was done on 30 Mei-30 Juni 2016. The result showed 73% had good knowledge, 27% had fair knowledge. This was due to almost all of families participate in BPJS of health could access the information easily, but not experienced in gaining benefit their participaton. A direct or indirect guidance of BPJS management to people were needed to be increasedso that people could get their right and follow the procedure.